Anti-aliasing for real-time applications in 3D using deep convolutional neural network - Siam, F. M. Jamius; Prince, Zahidul Islam; Bari, Ahmed Na sul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.